Inside Out or Outside In? On Criteria for Selecting Teachers of Religion, and the Case of the Druze. Issue 2 (14th March 2020) - Abbas, Randa; Court, Deborah
Abstract: This essay explores the issue of dress of teachers of Druze heritage. The Druze, among whom the rules of religious dress are rather specific, do not teach religion in schools, since the Druze religion is secret. The teacher acts as a gatekeeper and model. At the same time, Druze young people are becoming increasingly secular and may relate better to teachers who appear to be part of the modern world. This discussion examines the role of dress in teacher modeling, and the part Druze teachers may have to play in sustaining a small religion in rapidly changing times.